Task-based and resting-state fMRI reveal compensatory network changes following damage to left inferior frontal gyrus. (February 2018) - Hallam, Glyn P.; Thompson, Hannah E.; Hymers, Mark; Millman, Rebecca E.; Rodd, Jennifer M.; Lambon Ralph, Matthew A.; Smallwood, Jonathan; Jefferies, Elizabeth
Abstract: Damage to left inferior prefrontal cortex in stroke aphasia is associated with semantic deficits reflecting poor control over conceptual retrieval, as opposed to loss of knowledge. However, little is known about how functional recruitment within the semantic network changes in patients with executive-semantic deficits. The current study acquired functional magnetic resonance imaging (fMRI) data from 14 patients with semantic aphasia, who had difficulty with flexible semantic retrieval following left prefrontal damage, and 16 healthy age-matched controls, allowing us to examine activation and connectivity in the semantic network. We examined neural activity while participants listened to spoken sentences that varied in their levels of lexical ambiguity and during rest. We found group differences in two regions thought to be good candidates for functional compensation: ventral anterior temporal lobe (vATL), which is strongly implicated in comprehension, and posterior middle temporal gyrus (pMTG), which is hypothesized to work together with left inferior prefrontal cortex to support controlled aspects of semantic retrieval. The patients recruited both of these sites more than controls in response to meaningful sentences. Subsequent analysis identified that, in control participants, the recruitment of pMTG to ambiguous sentences was inversely related to functional coupling between pMTG and anterior superior temporal gyrus (aSTG) at rest, while the patients showed the opposite pattern. Moreover, stronger connectivity between pMTG and aSTG in patients was associated with better performance on a test of verbal semantic association, suggesting that this temporal lobe connection supports comprehension in the face of damage to left inferior prefrontal cortex. These results characterize network changes in patients with executive-semantic deficits and converge with studies of healthy participants in providing evidence for a distributed system underpinning semantic control that includes pMTG in addition to left inferior prefrontal cortex.